(untitled) (PUBMET, 2023)
Scholarly publishing is determined and guided by the questionable and artificial prestige of publication channels that are also falsely used for assessing the research and the researchers. This steers researchers to publish their papers in the same publication channels as others do, and many relevant channels are seen as less valuable. While publishing is focused on certain journals and publishers, open access publishing is increasingly concentrated on fee-based channels, where authors are obligated to pay publishing fees (article processing charges, APC and book processing charges, BPC) just to get their research published in open access. This places a burden for researchers to get funding for publishing; it creates inequality between the researchers with funding and those without it, and it increases the costs for universities and other research organizations. (See e.g., Klebel & Ross-Hellauer 2023.) At the same time the academic community has gone further from the very principles of open science, such as the attempts to control the increasing costs of scientific publications and the aims to improve the equality of researchers and other people in need of science. Diamond OA as a realistic alternative Open scholarly publishing should be funded in another way than by charging publication fees from individual authors or their institutions. Promoting Diamond OA should be seen as part of a larger change in the services and practices of scholarly publishing. The whole global academic community and research service providers should be engaged in this change. The current OA diamond landscape needs to be built as a community that will support diversity and include a wide range of different academic communities in different languages (see Becerril et. al., 2021). Research communities such as learned societies and research organizations could take more control of scholarly publishing. While universities are now advancing responsible research assessment (see CoARA), maybe it’s time to also reconsider the more active and responsible role of the universities in reforming the scholarly publishing sector. Case JYU Studies - open monographs with agile services JYU Studies is a fresh peer-reviewed monograph series for research affiliated with the University of Jyväskylä. We found a demand for an alternative publishing channel for peer- reviewed monographs with the Diamond OA model. The Open Science Centre of the University and the editorial board manage the series and the publishing process. The editorial work and publishing are funded by the Open Science Centre. Close and agile cooperation with the departments of the University and the authors is key to all successful publishing processes. • The peer-review process is implemented openly, so the authors and the reviewers are aware of each other’s identities. • We offer alternatives for publishing formats (such as Omeka S and EPUB) and develop publishing services in an agile way. • Our publishing services cooperate closely with our university researchers and listen to their thoughts and ambitions for publishing. • The publishing services include communication and marketing planning in cooperation with the authors striving to reach the best possible visibility for the publication. • We also offer the authors a reporting service showing the usage and visibility of publications (e.g., downloads, citations). This way, the publishing service continues after the publication, and the authors get interesting information about the visibility and impact of their publication. All monographs in JYU Studies are deposited in the University of Jyväskylä repository, JYX, which is an essential infrastructure for research and education at the university. Publishing in an open repository with high-quality metadata and registered DOI identifiers ensures that monographs are indexed in relevant databases.